(untitled) (Scientific journal of the Fergana State University, 2023)
The article analyzes an effective method for the synthesis of 1-phenyl azonaphthol-2 propargyl ether and its derivatives, as well as the physicochemical properties of the obtained substances.The paper presents the most optimal method for obtaining derivatives of 1-phenyl azonaphthol-2 propargyl ether (acetylenides of copper, silver, mercury derivatives).